MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN DI MI MADANI ALAUDDIN - Achruh, Andi; Sulaiman, Umar; Sabania, Mar’atun; Faridha, Nurul; Wulandari, Sri; Diansah, Ahmad (Educational Leadership: Jurnal Manajemen Pendidikan, 2025)
This research aims to determine the management of educational facilities and infrastructure in increasing learning effectiveness. The research objects are (1) Management of educational facilities and infrastructure; (2) Management of facilities and infrastructure in learning effectiveness; and (3) Obstacles and solutions for Facilities and Infrastructure Management at MI Madani Alauddin. The method used in this research is field research with a qualitative approach. Data was obtained in three ways, namely, interviews, observation and documentation. This research uses data analysis techniques, namely word reduction, data presentation and drawing conclusions. Based on the research results, it shows that; (1) The management of educational facilities and infrastructure has been implemented quite well. In this case, the institution has carried out planning, procurement, distribution, maintenance and elimination of educational facilities and infrastructure; (2) The implementation of learning becomes effective with the existence of facilities and infrastructure that facilitate it well; (3) Obstacles that occur are sought for solutions as soon as possible by the parties involved.